Employee Organizational Citizenship Behavior in The National Tire Industry: The Impact of Workplace Quality, Organizational Commitment, Career Development, and Entrepreneurial Orientation - Mohamad Zein Saleh; Dedi Purwana; Mohammad Rizan (Ridwan Institute, 2022)
Abstract This study intends to determine the direct and indirect effects of Quality of Work Life and Career Development on Organizational Citizenship Behavior via Organizational Commitment and Entrepreneurial Orientation. This research explains by evaluating hypotheses regarding the nature of the relationship and influence among factors. SEM (Structural Equation Modeling) analysis is utilized for statistical analysis. Results indicated that Quality of Work Life and Career Development positively influenced Organizational Citizenship Behavior; Quality of Work-Life positively influences Organizational Commitment; Organizational Commitment positively influences Organizational Citizenship Behavior; Career Development positively influences Entrepreneurial Orientation; Entrepreneurial Orientation positively influences Organizational Citizenship Behavior, and Quality of Work Life positively influences Organizational Commitment.